Gustav Klimt - Comini, Alessandra
The alluring art of Austrian artist Gustav Klimt (1862-1918) has seduced art lovers for decades. His decorative style, jewel-like colours, and sensuous line enchant the eye and the mind. The ornamental facades of his paintings pulsate with latent sexuality. Beneath the surface beauty exists a passionate commitment not only to the progress of painting, but to its relevance for society, which has made him, along with Egon Schiele and Oskar Kokoschka, one of Austria's three greatest modern artists. Comini discusses Klimt's portraits, allegories and landscapes as separate facets, tracing the development of each through to its culmination. She also explores the reverse parallel between Freud's and Klimt's approach: reversing Freud's process of interpreting dream symbolism to discover latent sexual content. Klimt began with the sexual forces he saw at work in the world and translated them into the sexual symbolism of his shimmering pain